2013
DOI: 10.2147/cia.s27717
|View full text |Cite
|
Sign up to set email alerts
|

Depression in the elderly with visual impairment and its association with quality of life

Abstract: BackgroundVisual impairment is more prevalent in the elderly and depression is common in this population. Although many studies have investigated depression or quality of life (QOL) in older adults with visual impairment, few have looked at the association between these two concepts for this population. The aim of this systematized review was to describe the association between depression and QOL in older adults with visual impairment.MethodsA search was done using multiple electronic databases for studies add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 95 publications
(160 reference statements)
5
56
0
2
Order By: Relevance
“…Social-psychological factors have been well documented to affect QOL of the elderly (Ibrahim et al, 2013;Li et al, 2004;Ouyang et al, 2009;Renaud & Bé dard, 2013;Tang et al, 2010;Xu et al, 2009Xu et al, , 2012Zhang et al, 2002). In this study, filial piety and neighborhood relationships were found to be associated with QOL in the urban elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Social-psychological factors have been well documented to affect QOL of the elderly (Ibrahim et al, 2013;Li et al, 2004;Ouyang et al, 2009;Renaud & Bé dard, 2013;Tang et al, 2010;Xu et al, 2009Xu et al, , 2012Zhang et al, 2002). In this study, filial piety and neighborhood relationships were found to be associated with QOL in the urban elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients with visual impairment have higher rates of depression and worse scores on quality-of-life scales than agematched controls. 9,10 Canadian law recognizes patient vulnerabilities in the patient-physician relationship and emphasizes the physician's fiduciary obligation to avoid conflict of duty and self-interest. 11 A 2014 report by the Ontario Health Coalition alleges that some ophthalmologist offices provided misinformation regarding medically necessary and unnecessary options, charged high fees to patients, and violated the Canada Health Act through extra billing and queuejumping.…”
Section: What Are the Unique Ethical Challenges?mentioning
confidence: 99%
“…An Asian comparative study identified stressful life event for a Thai population prior to the onset of depression, and found that any stressful life events, financial crisis, and serious illness were the three main events (Park et al, 2015). A systematic review revealed that older people with depression lowered the health related quality of life (Renaud & Bedard, 2013). The possibility of recurrence could occur even after more than a decade (Crona & Bradvik, 2012).…”
Section: Introductionmentioning
confidence: 99%